Prescription And Home Remedy of Gymnema Lactiferum (Sirukurincha) For Diabetes Mellitus (Neerilivu) In Jaffna - A Review - Sathiyaseelan, V.; Vijayakumar, T. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
The invaluable traditional anti-diabetic plants are sure to provide alternative therapeutic agents for diabetes. The genus Gymnema comprises 40 species. In Sri Lanka it is common in the dry and intermediate regions. Chewing the leaves destroys the ability to discriminate the sweet taste. Common name of the plant is sugar killer. Siddha text mentioned that Gymnema is the "Sarkaraikolli". Gymnema have been used by indigenous practitioners and public for the management of Diabetes mellitus in Jaffna. Previous scientific studies mentioned that the Tamil name of "Sirukurincha" is Gymnema sylvestre but the G. sylvestre is not available in Jaffna. Hence there is conflict situation in Jaffna regarding "Sirukurincha". The researchers searched solution for above problem. For the above objective, researchers made field visits, review of relevant documents, opinions from the plant related experts such as traditional practitioners, Senior lecturers, senior scientist, herbal gardens' MOICS, cultivators, personally interested public and Siddha medical students have interviewed for collecting existing and previous data. All the Previous studies of G. sylvestre and G. lactiferum searched related with Jaffna. Indigenous books, articles, journals, research papers reviewed. It is resulted that five scientific studies carried out in Jaffna. Four studies indicated that the available Gymnema species are the sylvestre and a study notified that the available species in Jaffna are the lactiferum with the evident for authentication of Royal botanical garden in Peradhenia. All government and private manufacturing centers for indigenous drug preparation are making three drugs that are contain "Sirukurincha" (lactiferum). Collected species from different places in Jaffna peninsula are the same plants and morphologically different or similar morphology. Differences noticed with organoleptic characters due the climates and soil texture. It is concluded that available Gymnema is lactiferum and it is used for the management of Diabetes mellitus in Jaffna.
Keywords: Sirukurinca; Gymnema; Prescription; Home remedy; Diabetes mellitus